Gosudarstvennoe upravlenie junozeskim sportom i ego podderzka - zalog uspesnogo vystupleniya sbornych komand Rossii na mezdunarodnom arene - Sysoev, V. I.; Germanov, G. N. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The state support of sports is the integral condition of its successful and effective functioning, and contruction of system of the measures accompanying its development, was fatally reflected in performances of athletes of the former socialist countries in the European arena. The aim of the research was to analyse the changes of sports results of 16-18 aged males and females representing the team of Russia (USSR) on the European championships on basketball in the various periods of social and economic development of the country and its influence on sports movement. The object of the research were Russian (USSR) male and female youth combined teams on basketball, prize-winners and finalists of championship of Europe among cadets and juvenals. The range placement was carried out for revealing changes of sports results of basketball teams - participants of the European championship among cadets and juvenals. The leadership of teams was determined by the least sum of the places occupied with them on the European championships. If the team in any championship did not get in number of 12 participants of final tournament, to it 13th place was given. The total sum of places was determined and the rating - an average settlement item place on results of participation in the championships came to light.